Proximate Determinants of Under-Five Mortality in Ethiopia: Using 2016 Nationwide Survey Data - Fikru C; Getnet M; Shaweno T (Dove Medical Press, 2019)
Chaltu Fikru,1 Masrie Getnet,2 Tamrat Shaweno1 1Department of Epidemiology, Faculty of Public Health, Jimma University Institute of Health, Jimma, Ethiopia; 2Biostatistics Unit, Department of Epidemiology, Faculty of Public Health, Jimma University Institute of Health, Jimma, EthiopiaCorrespondence: Tamrat Shaweno Email babiynos@gmail.comIntroduction: Although there has been a remarkable decline in under-five mortality through the decades, it is still highest in socio-economically disadvantaged countries, including Ethiopia. The benefits of reducing under-five mortality have been highly emphasized in the ambitious target of Sustainable Development Goals. The risk factors of under-five mortality have not been exhaustively researched in Ethiopia using recent nationwide survey data.Objective: This study aimed to determine the risk factors of under-five mortality using the recent nationwide survey data.Method: The data source for this study was the 2016 Ethiopian Demographic and Health Survey. Bivariate and multivariable logistic regression analysis was conducted and statistical significance was declared at p value < 0.05.Results: The data for a total of 10,641 under-five children were analyzed and the under-five mortality rate was 67 per 1000 live births in this study. In the final model, rural residence (AOR=2.0, [1.20, 3.30], P=0.008), mothers who gave birth with preceding birth intervals of shorter than 24 months (AOR=2.12, CI=[1.72, 2.61], P<0.000), multiple births (AOR=4.74, CI=[3.34, 6.69], P<0.000), very small size of child at birth (AOR=1.43, CI= [1.10, 1.85], P=0.007), and being male (AOR=1.30, CI=[1.07, 1.57], P<0.008) showed significant association with under-five mortality compared to their counterparts.Conclusion: Under-five mortality was significantly associated with place of residence, preceding birth interval, plurality, size of child at birth, and sex of the child. Thus, special emphasis should be placed on children with rural residence, preceding birth interval of shorter than 24 months, very small size of the child at birth, and male children.Keywords: under-five mortality, EDHS 2016, determinants, Ethiopia